2013
DOI: 10.1002/bsl.2051
|View full text |Cite
|
Sign up to set email alerts
|

Ten Year Research Update (2001–2010): Evaluations for Competence to Stand Trial (Adjudicative Competence)

Abstract: This article reviews and evaluates publications during 2001-2010 with relevance for assessments of competence to stand trial, referred to in this article as adjudicative competence. The review focuses specifically on articles that provide new concepts or data supported by research or case analyses. The studies are reviewed under the following headings: (i) systemic issues, (ii) conceptual guidelines for AC evaluations, (iii) AC assessment methods, (iv) empirical correlates of AC judgments and psycholegal abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 119 publications
1
17
0
Order By: Relevance
“…Individuals with schizophrenia and other psychotic disorders are at higher risk than those with mood disorders of incompetency findings (6), less likely to be restored to competency once found incompetent (7), and undergo longer related forensic hospitalizations (7, 8), which is highly consistent with the forensic hospitalization experience among the adults in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Individuals with schizophrenia and other psychotic disorders are at higher risk than those with mood disorders of incompetency findings (6), less likely to be restored to competency once found incompetent (7), and undergo longer related forensic hospitalizations (7, 8), which is highly consistent with the forensic hospitalization experience among the adults in our study.…”
Section: Discussionsupporting
confidence: 83%
“…A separate literature has examined the ability of forensic assessment instruments to distinguish between competent and incompetent defendants. Measures such as the MacArthur Competence Assessment Tool—Criminal Adjudication (MacCAT‐CA) and Evaluation of Competency to Stand Trial—Revised (ECST‐R) have shown promise as tools to inform evaluators' judgments of adjudicative competency (Fogel, Schiffman, Mumley, Tillbrook, & Grisso, ). However, surveys of practicing forensic evaluators suggest that these measures are rarely used.…”
Section: Introductionmentioning
confidence: 99%
“…63 Approximately onethird of individuals age 60 years or older who are referred for competency evaluations are deemed incompetent 64 and, compared to younger incompetent defendants, restoration rates for older individuals are much lower. 65 Frierson et al 66 compared geriatric defendants found incompetent to stand trial with their competent counterparts and found that the most common variables associated with incompetence were older age, presence of dementia, presence of other memory and concentration impairments, and deficits in orientation. Concerns over individual constitutional rights (eg, Jackson time limits) are elevated for competency determinations of elderly defendants as research shows that these defendants are unlikely to benefit from restorative treatment.…”
Section: Elderly Defendantsmentioning
confidence: 99%
“…Concerns over individual constitutional rights (eg, Jackson time limits) are elevated for competency determinations of elderly defendants as research shows that these defendants are unlikely to benefit from restorative treatment. 65 There is a need for additional research with elderly defendants to further develop our understanding of the implications of age and related impairments on competency evaluation and determination.…”
Section: Elderly Defendantsmentioning
confidence: 99%